Răspunsuri

Cel mai inteligent răspuns!
  • Utilizator Brainly
2014-11-12T14:46:46+02:00
a)(x+2y)²=x²+4y²+4xy
b)(y+x)²=y²+x²+2xy
c)(a+0,7)²=a²+0,
49+1,4a
d)(3+y)²=9+y²+6y
e)(2,5-2y)²=6,
25+4y²-10y
f)(1,6+b)²=2,
56+b²+3,2b
g)(4a-3b)²=16a²+9b²-2
4ab
h)(2a-5b)²=
4a²+25b²-20ab
i)(c-0,5a)²
=c²+0,25a²+ac

10 4 10
spunea*
unde*
Comentariul a fost şters
Tot prost esti mai bun e cel a lui Corciu1999 dar lasa asa
:)
2014-11-12T15:01:48+02:00
A) (x+2y)²= x²+2x·2y+(2y)²=x²+2x·2y+4y²
b)(y+x)²=y²+2yx+x²
c)(a+0,7)²=a²+2a·0,7+(0,7)²=a²+1,4a+0,49
d) (3+y)²=3²+2·3y+y²=9+6y+y²
e)(2,5-2y)²=(2,5)²-2·2,5·2y+(2y)²=6,25-10y+4y
f) (1,6+b)²= (1,6)²+ 2· 1,5b +b²=2,56 +3b+b²
g) (4a-3b)²= (4a)² - 2 ·4a·3b+(3b)²= 16a- 24ab+9b
h) (2a-5b)² = (2a)² - 2·2a ·5b +(5b)²= 4a-20ab +25b
5 4 5